Transformasi Digital Manajemen Aset Pendidikan: Implementasi Sistem Informasi Sarana dan Prasarana Terintegrasi pada SMK Pancasila 1 Kutoarjo - Wahid Nur Rohman (Jurnal Ekonomi dan Teknik Informatika (JNETI), 2026)
Digital transformation in educational institutions has become a strategic imperative to enhance operational efficiency and accountability. SMK Pancasila 1 Kutoarjo faces significant challenges in infrastructure and asset management, which remains manual and fragmented, leading to data redundancy and delayed inventory reporting. This study aims to design and implement an Integrated Asset and Infrastructure Information System to optimize school governance. The research methodology employed is Research and Development (R&D) using the Waterfall development model, encompassing requirements analysis, system design, coding, and testing. The results indicate that the implementation of the integrated system significantly reduces the asset reporting cycle time from several working days to mere minutes via real-time data access. Furthermore, data synchronization across departments (workshop heads and infrastructure units) improved inventory accuracy to 100% and strengthened decision support for school management in procurement planning. This study concludes that the digital transformation of asset management serves as a critical instrument for Vocational High Schools (SMK) in managing complex practical equipment effectively and transparently.